2020
DOI: 10.1177/0013916520937455
|View full text |Cite
|
Sign up to set email alerts
|

In Cold Weather We Bark, But in Hot Weather We Bite: Patterns in Social Media Anger, Aggressive Behavior, and Temperature

Abstract: Hotter weather is associated with aggressive crime. However, it is not well known if similar relationships apply to online aggression. This study uses anger counts derived from Twitter posts (tweets) and assault counts in New South Wales, Australia, to investigate if they share a similar relationship with temperature, and to determine if online anger is a predictor of assault. Results indicated that the relationships were largely inverse—assault counts were higher in summer than winter, while angry tweet count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…These results are echoed by Younan et al’s [ 14 ] findings that long-term exposure to high ambient temperatures is associated with aggressive behaviors in children and adolescents in urban areas. Similarly, using data from South Wales, Australia, Stevens et al [ 15 ] found a similar effect of high temperatures on assaults. However, the authors found that high temperatures were associated with a decrease in anger expressed in social media, as measured by counts of angry tweets.…”
Section: Introductionmentioning
confidence: 80%
“…These results are echoed by Younan et al’s [ 14 ] findings that long-term exposure to high ambient temperatures is associated with aggressive behaviors in children and adolescents in urban areas. Similarly, using data from South Wales, Australia, Stevens et al [ 15 ] found a similar effect of high temperatures on assaults. However, the authors found that high temperatures were associated with a decrease in anger expressed in social media, as measured by counts of angry tweets.…”
Section: Introductionmentioning
confidence: 80%
“…But not all studies found that negative outcomes are caused by hot temperature (Stevens et al, 2021). Russia, Afghanistan, and South Africa are not hot countries, but they all have high domestic violent prime rates (Potgieter et al, 2022).…”
Section: Empirical Studies On Temperature and Aggressive Behaviormentioning
confidence: 99%
“…But average temperature is a flawed proxy of demanding thermal climate (Fischer and Van de Vliert, 2011;Van de Vliert, 2013a,b). The main reason is that hotter-thantemperate and colder-than-temperate temperature posed different challenges for humans and consequently showed different effects on human psychological dispositions and behavior (Murray, 2013;Van de Vliert, 2013b;Stevens et al, 2021). For humans 22°C is the most comfortable temperature under which the needs for nutrition and health can be more easily met.…”
Section: Cold and Heat Demandsmentioning
confidence: 99%
“…Weather factors can affect investor behavior by altering investor risk aversion behavior, emotion, and cognitive output (Cheema & Patrick, 2012; Heyes & Saberian, 2019; Kathiravan et al., 2021; Keef & Roush, 2007; Stevens et al., 2021). We have proven that the influence of high temperature on land transaction price is significantly positive.…”
Section: Behavior Channels Of High Temperature On Land Transactionmentioning
confidence: 99%
“…On the physiological dimension, exposure to high temperature will reduce blood flow to the brain, increase heat‐related fatigue, and decrease the ability of concentration and memory (Hocking et al., 2001; Kiyatkin, 2007). On the perceived dimension, the influence of climate on cognitive output has been well‐studied in recent years (K. B. Anderson et al., 1998; Heyes & Saberian, 2019; Hu & Li, 2019; Miles‐Novelo & Anderson, 2019; Stevens et al., 2021). Therefore, the risks of climate change are analyzed from multiple perspectives.…”
Section: Introductionmentioning
confidence: 99%